Unveiling the menstrual mind: Exploring proprioceptive proficiency, reaction responsiveness, and motor mastery in premenstrual syndrome versus Non-PMS cohorts: A two-arm parallel non-blinded cross-sectional study - Anshu Sharma; Simranjeet Kaur; Parveen Kumar; Nidhi Sharma (Elsevier, 2024)
Introduction: Premenstrual syndrome (PMS) is characterized by cyclical physical and mood disturbances during the luteal phase. Symptoms gradually intensify during this phase and typically subside a few days after menstruation begins. PMS encompasses neuromuscular and psychological symptoms that can significantly affect the quality of life of affected females. This study aims to compare proprioception, reaction time, and coordination between females with PMS and those with non-PMS. Material and methods: A cross-sectional study, conducted in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines, recruited 998 females with PMS and without PMS, aged 18-40 years based on premenstrual dysphoric disorder criteria. Participants underwent assessments of proprioception and reaction time using the Sensbalance Miniboard. Coordination was assessed using Lower Extremity Motor Coordination Test. Data analysis utilized the Kolmogorov-Smirnov test to determine the normality of the data while Mann Whitney-U test was used to compare the between group differences of the variables. Results: Significant differences were observed with p-value <0.05 for all the variables, proprioception (front, back, right and left), reaction time (front, back, right and left), coordination (right and left) between the PMS and non-PMS groups. Conclusions: Females with PMS were associated with great variation in proprioception, reaction time and coordination when compared with females without PMS.